An Indian View of an Indian View: Durrell’s India - Gulshan Taneja (Études Britanniques Contemporaines, 2011)
Lawrence Durrell’s India connection has always been made much of. After all, he was born in India. Durrell even had parents who were both born in India, too, and spoke Hindi and Urdu. He nostalgically spoke about India all his life. He wrote a great deal about his fascination with India to his many correspondents in his letters. India lies scattered throughout his writing. Indian myths, motifs and icons can be found generously sprinkled in his narratives. More so, Durrell succumbed to the idea of India as it had been nourished and cherished over hundreds of years as part of the English imagination: the India of the Orient. He even wrote an autobiographical novel with a full third describing the ordinary life of an ordinary human being in an ordinary country drawing upon his experiences in India. No wonder Durrell scholars, readers, and interpreters share a widespread perception of an Indian aura in Durrell’s life and writings with a great deal of enthusiasm. One would, thus, expect much substance in Durrell’s view of India and expect to be able to put together a perceptive and a meaningful critique of India and its people based on his writings. But the exercise is fraught with many difficulties and the conclusions are more than disappointing and thwart all expectations.